Comparative transcriptome analysis of adult worker bees under short-term heat stress - Zhang, Bing; Li, Xinyu; Jiang, Yusuo; Liu, Jinjia; Zhang, Jiangchao; Ma, Weihua (Frontiers in Ecology and Evolution, 2023)
High temperatures affect behavior, physiology, survival, and the expression of related genes in adult honeybees. A. mellifera is the common pollinator in greenhouse and is susceptible to high temperature stress. To further explore the molecular basis related to heat stress, we compared the transcriptome profiles of adult worker bees at 25 °C and 45 °C, and detected the expression patterns of some differentially expressed genes (DEGs) in different tissues by q RT-PCR. Differential expression analysis showed that 277 DEGs were identified, including 167 genes upregulated and 110 genes downregulated after heat stress exposure in adult worker bees. In GO enrichment analysis, DEGs were mostly enriched for protein folding, unfold protein binding, and heme binding terms. Protein processing in endoplasmic reticulum and longevity regulating pathway-multiple species were significantly enriched in KEGG. The expression levels of 16 selected genes were consistent with the transcriptome results. The expression patterns of 9 DEGs in different tissues revealed high levels in the thorax, which was supposed that the thorax may be the most important part in the response to heat stress. This study provided valuable data for exploring the function of heat resistance-related genes.